2003
DOI: 10.1023/b:ejep.0000040531.77638.17
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variability in Population Acute Myocardial Infarction Cumulative Incidence and Mortality Rates in Spain 1997 and 1998

Abstract: MI cumulative incidence and mortality rates are low compared with other industrialized countries but, vary considerably among regions in a Mediterranean country like Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
2
14

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 20 publications
(24 reference statements)
1
23
2
14
Order By: Relevance
“…[14][15][16][17][18][19][20] Furthermore, AF is an important disease entity which is directly related to recurrent systemic thromboembolic events, especially cerebral infarction, HF, and bleeding events provoked by longterm antiplatelet agent or anticoagulant prescription, especially in elderly populations. 19) About 30% of strokes in patients older than 70 years originate purely from AF.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Furthermore, AF is an important disease entity which is directly related to recurrent systemic thromboembolic events, especially cerebral infarction, HF, and bleeding events provoked by longterm antiplatelet agent or anticoagulant prescription, especially in elderly populations. 19) About 30% of strokes in patients older than 70 years originate purely from AF.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24] However, most of these studies focused on specific regions of Spain or covered incident cases from the 1990s, before troponin analysis was routinely used in the diagnosis of acute myocardial infarction. Because of these limitations, we decided to draw on the information in the Spanish Registry of Hospital Discharges (Minimum Basic Data Set), 25 which has been used in several studies on acute myocardial infarction.…”
Section: Acute Coronary Syndromementioning
confidence: 99%
“…The recalibrated risk function provided estimates that better matched but still slightly overestimated the projected number of events, except for a large overestimation in women aged over 65. A possible explanation is the fact that the Swiss case-fatality rate used to compute the number of cases was only 12%, which is very low compared to the literature [43,44] and might have artificially inflated the number of events. Indeed, increasing case-fatality rates to 25%, a more reasonable [43] estimate, led to more consistent results (Table 3), while increasing case-fatality rates to 44% as reported by others [44] led to an overestimation of the number of events.…”
Section: Discussionmentioning
confidence: 98%
“…A possible explanation is the fact that the Swiss case-fatality rate used to compute the number of cases was only 12%, which is very low compared to the literature [43,44] and might have artificially inflated the number of events. Indeed, increasing case-fatality rates to 25%, a more reasonable [43] estimate, led to more consistent results (Table 3), while increasing case-fatality rates to 44% as reported by others [44] led to an overestimation of the number of events. Still, sensitivity analysis showed that this overestimation was relatively small within a reasonable range of mortality and case-fatality rates, as compared to the original Framingham function.…”
Section: Discussionmentioning
confidence: 98%